Inovasi Metode Role Playing Materi Pernikahan Dalam Islam Mata Pelajaran PAI di SMK Mifathul Ulum Tanjungarum Sukorejo Pasuruan - Farah, Dewi Farah Adibah; Muhammada; Ahmad Ma’ruf; Achmad Yusuf; Nur Rokhmatullah (IAIN Ambon, 2024)
Role playing method has been an innovation in learning marriage islam subject islamic education. This research goal for activities learning method improve understanding student about draft of marriage islam and promote social skill. Role playing method implicate student in role different simulation vibes wedding, allows them to theory apply islamic practically. Research use qualitative approach with classroom observations, interviews with students, and analye for impact evaluation role playing method.the result explain method student increase, deepen their understanding of marriage in islam values, and develop communication and problem-solving. Students demonstrated a high level of statisfaction with this learning experience and expressed an increase in their understanding of the concept of islamic marriage. This research recommends that the role playing method can be an effective tool in teaching islamic marriage material in PAI subject, providing and enjoyable experience for students.